Rancang Bangun Sistem Informasi Tugas Akhir Dengan Pengujian Fungsional Blackbox Testing Di Fakultas Sains Dan Teknologi Universitas Jambi - Susanto, Andy (JUSS (Jurnal Sains dan Sistem Informasi), 2024)
The final project process which is managed by the faculty of science and technology at the University of Jambi is currently considered ineffective and inefficient because there are some human errors and documentation that is still done manually will experience difficulties in the future. Therefore this research was conducted to provide solutions to these problems by building information systems that can overcome various processes and problems that have been encountered. The information system development method used in this study is the prototype method. The protoype method consists of 5 stages namely communication, quick plan, quick design modeling, construction of prototype, and deployment, delivery and feedback. In addition the system built will be tested in the form of functional testing using blackbox testing. Functional testing is done by testing the functions on the system by running a test scenario whether the functions on the system are as expected or not. The results of the study using blackbox testing showed that this system was functionally running as expected.